Aktivitas Immunodulator Ekstrak Etanol Umbi Bawang Merah (Allium cepa L.) terhadap Respon Imun Non Spesifik pada Mencit Jantan Galur BALB/C dengan Metode Carbon Clearance - Diska Anggraeni Alfitasari; Anjar Mahardian Kusuma; Zainur Rahman Hakim (Fakultas Biologi | Universitas Jenderal Soedirman, 2017)
The content of flavonoids on onion useful to maintain endurance. This research aims to know the activity of exstract immunodulator of onion bulb ethanol (Allium cepa L) on phagocytic activity in male mice balb/c with varian dose and campored immunodulator activity with positive control. This study is an experimental reseach with Completely Randomized Design (CRD). Preparation of extract ethanol onion roots done by maceration using 96% ethanol for 9 hours. The test performed on samples which consist of 25 mice with carbon clearance method, devided into 5 groups, which are : K – (without treatment), k+ (with imboos 13,3 ml/Kg Bw), P1 (dose 12%), P2 (dose 24%), and P3 (dose 48%). The test performed for 5 days, and on the 7th day injected carbon (pelicans) as much 0,1 ml/ 10 gr Weight intravenousty, their blood taken before carbon injection (minute 0) and minute 4, 8, 12, and 16. After their transmittance measure using spectrophotometer at 600,5 nm wavelength. This research shows that extract ethanol of onion balb has immunodulator activity effect on non-specific immune response on male mice balb/c with carbon clearance method. The dose of 12% (v/v), 24% (v/v) and 48% (v/v) dose have lower immunostimulatory capacity than positive control.